The Denier in Chief: Faith in Trump and Techniques of Neutralization in a Pandemic. Issue 7 (3rd July 2022) - Cullen, Francis T.; Graham, Amanda; Jonson, Cheryl Lero; Pickett, Justin T.; Sloan, Melissa M.; Haner, Murat
ABSTRACT: Based on a March 28–29, 2020 MTurk survey (N = 1, 000), the current study examined how faith in President Donald Trump's statements downplaying the risks and his responsibility for the COVID-19 pandemic affected endorsement of social distancing techniques of neutralization. Controlling for a host of variables, the analysis revealed that faith in Trump's denials was robustly associated with neutralization beliefs. Support for techniques of neutralization also was affected by, among other variables, low self-control and binding foundations, a construct drawn from Haidt's Moral Foundation Theory. These results suggest that in the early stages of the pandemic, President Trump's denials served as a likely source of cognitions justifying noncompliance with social distancing health norms. More generally, the data indicate that in his assumed role of the "Denier in Chief, " Trump may have been influential in prompting faithful followers to engage in conduct (e.g., be maskless, associate indoors) that exposed them to coronavirus infection as the pandemic unfolded throughout 2020.